Impact of stocking densities on growth, organ index, serum biochemistry, gut morphology and microbiota of young ducks in a rice-duck-crayfish coculture system - Xiao Long He; Zhen Hua Liang; Ze Heng Huang; Lian Bing Qi; Yan Wu; Jia Liu; Tao Huang; Jing Bo Liu; Jin Song Pi; Hao Zhang (Animal Bioscience)
Objective The rice-duck-crayfish (RDC) coculture system, an ecologically efficient breeding strategy that accommodates natural behavior of ducks and improves their welfare. The optimal stocking density and its impact on duck health in this system remains undetermined. The study examined the impact of stocking densities on growth, organ index, serum biochemistry, gut morphology and microbiota of ducks in RDC system. Methods A total of five hundred and forty 20-day-old Nonghu No. 2 ducks were randomly allocated based on density: low-density (LD; 8 birds/666.67 m2), medium-density (MD; 12 birds/666.67 m2) and high-density (HD; 16 birds/666.67 m2) groups, with three replicates in each group, and the symbiosis period was up to 40 days until rice tasselling. Results There were no significant differences in final body weight, average daily gain, or feed:gain ratio between groups (p>0.05); however, the liver and spleen indices of ducks in HD group were significantly greater than those in LD group (p<0.05). The serum albumin concentration in HD group decreased, whereas creatine kinase activity increased (p<0.05). Additionally, the ileal crypt depth significantly increased and the ileal villus height and villus/crypt ratio significantly decreased in ducks in MD and HD groups compared to LD group (p<0.05). Moreover, the abundance of cecal Deferribacterota and Spirochaetota increased significantly (p<0.05), while the abundance of Firmicutes decreased significantly (p<0.05) with increasing stocking density. Moreover, the increase in stocking density significantly decreased the abundance of some beneficial bacteria (Faecalibacterium and Fournierella) and increased the abundance of some harmful bacteria (Mucispirillum and Brachyspira) (p<0.05). Conclusion These results suggest that moderately HD breeding doesn’t significantly affect duck growth, but increased stocking density led to changes in cecal microbiota and dysbiosis. Reducing stocking density positively affects immune parameters and ileum morphology. However, due to the limited number of total replicates of the study, further research is needed to validate the reliability of the results.